Intercultural Communication in the Perspective of Gender - Aridah Aridah (Journal of English as A Foreign Language Teaching and Research, 2021)
Intercultural communication is usually viewed as the communication which takes place between two or more people from different cultural backgrounds. These different cultural backgrounds are commonly understood as different languages and nationalities. However, intercultural communication is not limited to these backgrounds. It can also be viewed as communication across gender. This article aims to provide a conceptual study which reviews some ideas regarding intercultural communication in the view of gender. It discusses the ideas proposed by some scholars in communications concerning how men and women communicate differently because they are considered members of different cultures, that is, the culture of men and the culture of women. The discussion focuses on the differences between men and women in terms of communication styles, communication attitudes, and linguistic strategies. Some potential misunderstandings which occur between men and women are also presented as a result of those differences.